Detecting Asset Price Bubbles: A Multifactor Approach - Tomfort, Andre (International Journal of Economics and Financial Issues, 2017)
Asset price bubbles and deep financial crises have occurred frequently over the past three decades. No wonder that decision makers are searching for ways to protect their economies. Recognizing price bubbles in time could be very helpful in this regard to implement countermeasures such as higher interest rates, taxes or capital buffers. In this paper a solution to this problem shall be proposed: a multifactor valuation approach based on a discounted cash flow and a cointegration model that links asset prices with selected variables to determine the valuation of a market. In addition, the gaps of credit and private fixed investments to GDP are measured to assess whether the economy is facing overleveraging and overinvestment. If the four measures lead to a clear picture, policy makers are advised to take action. An exemplary analysis has been done for the former bubbles in Japan, and in the US stock and housing market. Keywords: Asset Price Bubbles, Cointegration, Credit and Investment Expansion JEL classifications: E44, G01, G15, G17